Mesenchymal stem cells/multipotent stromal cells (MSCs) are glycolytic and thus glucose is a limiting factor of in vitro models of MSC starvation - Nuschke, Austin (Stem Cell Res Ther, 2016)
BACKGROUND: Mesenchymal stem/multipotent stromal cells (MSCs) contribute to tissue repair but are challenged during wound healing when the blood supply is disrupted, thereby limiting nutrient delivery. Survival mechanisms against ‘starvation’ include autophagy, which we previously found to enhance differentiation efficiency. MSC response to models of in vitro nutrient deprivation are of great interest for improving MSC survival and therapeutic efficacy; however, the rate-limiting nutrients are unknown. METHODS: MSC responses to culture nutrient and/or serum deprivations were assessed through light microscopy, cell survival, and measurements of metabolic levels. Glucose uptake was determined through conditioned media analyses over 3 days of culture. The Seahorse XF24 Flux analysis system was used to determine oxygen consumption and extracellular acidification for glycolytic metabolism. MSC autophagic response to these conditions was assessed via immunoblots for LC3-I and LC3-II, markers of autophagosome turnover. RESULTS: We more closely examined limiting nutritional factors to MSC survival in vitro, finding that glucose is rapidly utilized/depleted whereas amino acids and other required nutrients were used sparingly. This finding concurred with metabolic analyses that showed a primarily glycolytic character to the MSCs at steady state. MSC autophagy, previously linked to MSC function through a unique accumulated autophagosome phenotype, also responded quickly to changes in glucose concentration, with drastic LC3-II changes within 24 h of glucose concentration shifts. CONCLUSIONS: Our results demonstrated a rapid uptake of glucose in MSC cultures that was due to a highly glycolytic phenotype for the cells; MSC starvation with serum or other nutrients appears to have a less notable effect on the cells. These findings highlight the importance of glucose and glucose metabolism on MSC function. The conditions and cellular responses outlined here may be essential in modeling MSC nutrient deprivation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-016-0436-7) contains supplementary material, which is available to authorized users.